Notes on Small Animal Dermatology. - Joyce, Judith (John Wiley & Sons, 2011)
Part of the popular 'Notes On' series, this book is full of practical advice and information on diagnosing and treating common dermatological problems in small animals. The rapid reference format is designed to help you locate information as quickly as possible. Information on common dermatological complaints is offered in different ways to meet a variety of needs. Firstly a problem-orientated perspective is provided, and then a disease-based perspective looking at what underlying problems cause particular diseases. This is followed by a section that looks at dermatological disease by anatomic.